Isolation and Toxin Gene Profiling of Clostridium difficile from Environmental Samples in Andhra Pradesh, India - N. Nagarjuna Reddy; T. Srinivasa Rao; CH. Bindu Kiranmayi; CH. Sudha Rani (The Indian Veterinary Journal, 2025)
This study investigates the presence of Clostridium difficile in environmental samples, specifically farm soil (25) and farm water samples (25). A total of 50 samples were collected from nearby poultry (02), sheep farm regions (02) and pig rearing areas (02) areas and analyzed with cultural tests identifying 8 isolates (16.0%) were positive for C. difficile. PCR testing revealed a lower detection rate, with 2 isolates (4.0%) positive for the tpi (Species specific) gene. Further analysis of isolates for the presence of virulent genes revealed presence of toxin A and toxinB and binary toxin (cdtA and cdtB). These findings underscore the potential environmental reservoirs of C. difficile, highlighting the need for further research to drive into their ecological impact and implications for public health. The presence of C. difficile in farm soil and water samples suggests that this pathogen may be disseminated through these environmental sources. However, data on C. difficile in environmental samples is limited. Therefore, comprehensive research is necessary to investigate the prevalence of C. difficile in food animals and on various environmental surfaces.